Can the botanical azadirachtin replace phased-out soil insecticides in suppressing the soil insect pest Diabrotica virgifera virgifera? - Stefan Toepfer; Szabolcs Toth; Mark Szalai (CABI Agriculture and Bioscience)
Abstract Background Due to recent bans on the use of several soil insecticides and insecticidal seed coatings, soil-dwelling insect pests are increasingly difficult to manage. One example is the western corn rootworm (Diabrotica virgifera virgifera, Coleoptera: Chrysomelidae), a serious root-feeder of maize (Zea mays). We investigated whether the less problematic botanical azadirachtin, widely used against above-ground insects, could become an option for the control of this soil insect pest. Methods Artificial diet-based bioassays were implemented under standard laboratory conditions to establish dose response curves for the pest larvae. Then, potted-plant experiments were implemented in greenhouse to assess feasibility and efficacy of a novel granular formulation of azadirachtin under more natural conditions and in relation to standard insecticides. Results Bioassays in three repetitions revealed a 3-day LD50 of 22.3 µg azadirachtin/ml which corresponded to 0.45 µg/neonate of D. v. virgifera and a 5-day LD50 of 19.3 µg/ml or 0.39 µg/first to second instar larva. No sublethal effects were observed. The three greenhouse experiments revealed that the currently proposed standard dose of a granular formulation of 38 g azadirachtin/hectare for in-furrow application at sowing is not enough to control D. v. virgifera or to prevent root damage. At 10× standard-dose total pest control was achieved as well as the prevention of most root damage. This was better than the efficacy achieved by cypermethrin-based granules and comparable to tefluthrin-granules, or thiamethoxam seed coatings. The ED50 for suppressing larval populations were estimated at 92 g azadirachtin/ha, for preventing heavy root damage 52 g/ha and for preventing general root damage 220 g/ha. Conclusions There seems clear potential for the development of neem-based botanical soil insecticides for arable crops such as maize. They might become, if doses are increased and more soil insecticides phased out, a promising, safer solution as part of the integrated pest management toolkit against soil insects.